The structural basis for the pathophysiological relevance of PAI-1 in cardiovascular diseases and the development of potential PAI-1 inhibitors - Gils, Ann; Declerck, Paul J. (Thrombosis and Haemostasis, 2004)
Plasminogen activator inhibitor-1 (PAI-1) is an important component of the plasminogen/plasmin system as it is the main inhibitor of tissue-type and urokinase-type plasminogen activator. Consequently, PAI-1 plays an important role in cardiovascular diseases (mainly through inhibition of t-PA), and in cell migration and tumor development (mainly through inhibition of u-PA and interaction with vitronectin). As a member of the serpin superfamily, PAI-1 shares important structural properties with other serpins. However, PAI-1 also exhibits unique conformational and functional properties. The current review provides an overview of the knowledge on PAI-1 gathered since its discovery two decades ago. We discuss (a) its structural properties of the protein and their subsequent relation to functional activities, (b) its role in a wide variety of (patho) physiological processes and (c) a number of strategies to interfere with its functional properties eventually aiming at pharmacological modulation of this risk factor.
Keywords: PAI-1; serpin; fibrinolysis; thrombosis